Immigration, lawlessness and the gap between discrimination and the allowed distinction - García, Lila (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
In the Framework of an alarming rising of international illegality, several States argue that immigration or the irregular stay to carry out limitations or clear abolition in regard to the exercise of rights. The question is How we build the parameters to make a difference between which in certain cases constitutes, or not, discrimination. In other words, when the fact of being national or alien can be a valid —in terms of law, as not prohibited— reason, or «the» ground, of a public policy that exclude or restrict in some manner the protection and enjoyment of the rights, and if so, relating which rights in particular. After a short tour over the three principal elements that came into play (State, immigration, human rights), this work delimits an attempted catalogue of certain rights do arguable to determine, to their respect, in which extension the circumstance of being foreigner or illegal immigrant can be held up legal measures to protect public security, rights of citizens or public order, for example
Keywords: Migration; Aliens; Discrimination; Human Rights